IMPLEMENTASI KEBIJAKAN TENTANG PENGENDALIAN LINGKUNGAN HIDUP DI TAMAN MARGASATWA KOTA SEMARANG - Rachmawati, Henny; Hidayat, Zaenal; Rostyaningsih, Dewi (Journal of Public Policy and Management Review, 2013)
In reducing environmental pollution, Semarang municipality has made a local regulation number 13 on the year of 2006 on environmental control. It was intent to environmental control for reducing its pollutions that caused by organic wastes as wellas inorganic one. Because, it can have a effect negatively for human and animals who are getting in, and the gases those are coming from decomposition, combustion or evendisposal process interfere health as well. The office of technical implementing got target for realizing environmental wildlife park which to be clean an health.The reasearch used a descriptive qualitative method that lovated on the area of Semarang wildlife park and focus on its policy implementation of environmental control. There were two data sources such primary and secondary. Its instruments usedas research instrument, interview guide, and informant. The way how to determine its technique that applied snowball sampling while collecting data using interview, observation, and library reasearch to get the whole data. Afterwards this analysis usingthe technique of domain and taxonomic data analizes.There were four phenomena which observed on this study. They were implementation policy by the factors of communications, resources, and stances. From the research, policy implementation has been running well. Where as communication and stances had been done very good, that by socializing those policy and supported its regulations as well. However this needed more staffs to fulfill this kind of implementations. This regulations was very substantial for producing environmentallyare clean and free of contaminations.